Associated risk factors for acute urinary retention among patients presenting with benign prostatic hyperplasia at a tertiary care hospital in Nepal (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Acute urinary retention (AUR) is an important public health issue in older male population with benign prostatic hyperplasia (BPH). Various risk factors are associated with increased incidence of AUR among patients with BPH being managed conservatively.Method: A retrospective analysis was performed AUR with BPH among patients in Shree Birendra Hospital (SBH), Chhauni, Kathmandu, Nepal for a period of one year. Study variables included patient age, serum prostate specific antigen (PSA), prostate volume, history of AUR, smoking, diabetes mellitus, hypertension, cardiovascular disease, and other comorbid diseases. The SPSS was used for data analysis, X2 test to find out the association and a p